The impact of climate changes on surface water resources in Libya using spatial techniques: An applied study on the Wadi Ka'am Basin for the period 1981-2020 (Journal of Human Sciences, 2024)
The research aims to evaluate the impact of climate change on surface water resources in Libya by analysis and tracking the time series of water quantities collected in the Wadi Ka'am Dam and their relationship to temperature, analysis the trends of change in rainfall amounts, determining the variation in their amounts using statistical analysis. In addition, employing spatial techniques to understand the impact of climate change on the water cycle and its future changes by 2050 in the Wadi Ka'am Basin. The study concluded that there is a trend towards a decrease in the average annual rainfall amounts in the study area without statistical significance. The decrease amounts ranged between 22.05 mm in Tarhuna and 32.81 mm in the Al-Khoms area, about 30.19 mm in the Kaam area, and with a trend of increase appearing in favor of the second period by about 30.89 mm in the Lamamra area, The results also indicated that there were differences in the average minimum and maximum annual temperature between the two periods of the study in favor of the period. The second temperature in all monitoring points ranged between 0.562°C and 0.806°C, in the Al-Khoms and Zliten stations, respectively, at a level of statistical significance less than 0.001 in all stations for the period 1981-2020, The Wadi Kaam Basin will witness a decrease in surface runoff and soil moisture, and actual evaporation rates will increase in the Wadi Kaam Basin to reach between 205.7-225.2 mm/year by 2050.